Challenges in developing competency-based training curriculum for food safety regulators in India - Anitha Thippaiah; Komal Preet Allagh; G V Murthy (Wolters Kluwer Medknow Publications, 2014)
Context: The Food Safety and Standards Act have redefined the roles and responsibilities of food regulatory workforce and calls for highly skilled human resources as it involves complex management procedures. Aims: 1) Identify the competencies needed among the food regulatory workforce in India. 2) Develop a competency-based training curriculum for food safety regulators in the country. 3) Develop training materials for use to train the food regulatory workforce. Settings and Design: The Indian Institute of Public Health, Hyderabad, led the development of training curriculum on food safety with technical assistance from the Royal Society for Public Health, UK and the National Institute of Nutrition, India. The exercise was to facilitate the implementation of new Act by undertaking capacity building through a comprehensive training program. Materials and Methods: A competency-based training needs assessment was conducted before undertaking the development of the training materials. Results: The training program for Food Safety Officers was designed to comprise of five modules to include: Food science and technology, Food safety management systems, Food safety legislation, Enforcement of food safety regulations, and Administrative functions. Each module has a facilitator guide for the tutor and a handbook for the participant. Essentials of Food Hygiene-I (Basic level), II and III (Retail/ Catering/ Manufacturing) were primarily designed for training of food handlers and are part of essential reading for food safety regulators. Conclusion: The Food Safety and Standards Act calls for highly skilled human resources as it involves complex management procedures. Despite having developed a comprehensive competency-based training curriculum by joint efforts by the local, national, and international agencies, implementation remains a challenge in resource-limited setting.